Catch-enrich-release approach for amine-containing natural products. Issue 90 (20th October 2022) - Müller, Michelle Jessy; Dorst, Andrea; Paulus, Constanze; Khan, Imran; Sieber, Simon
Abstract : Chemoselective approach to extract amine-containing natural products from complex matrices. The enzymatic release from the probe affords the underivatised compounds as products. Abstract : Amine-containing natural products are an important class of therapeutic compounds. Herein, we report a chemoselective approach to catch and enrich amine-containing natural products, and release them as underivatized compounds. The strategy exploits the selectivity of the enzyme legumain for the specific release of amine-containing natural products.